Why do I Follow the Program KB? (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
The behavior of mothers who want to become KB acceptor is interesting to be known and studied, considering the many negative views or perception about family planning such as: KB can disturb fertility, contrary to family planning, KB can disrupt health, the view that many children can bring a lot of fortune and etc. This study aims to Explores in depth the factors that pushed the mother into KB acceptor at clinic image of Pratama Citra Husada Kupang. Qualitative research with exploratory design and phenomenology approach. The main informants were mothers who became KB acceptor and supporting informants were the clinic head, BKKBN representative of NTT province and field officer of KB. Data collection is done by: 1. Observation; 2. In-depth interview. Factors that encourage mothers to accept family planning acceptors are: Do not bother to take care of children, Fear when pregnant again with close distance, Mother is in a state of urgency, Consider the child’s education forward, Child’s health is assured and affection to the child can be maximal, Experiencing Trauma in childbirth, To be more successful in the future, consider economic factors and for maternal and child health. Family Planning Program is beneficial for mothers, both physically and psychologically. Mothers who are not yet acceptor of KB need to consider joining family planning program because the benefits of family planning have been very proven in society.